Graphene-supporting films and low-voltage STEM in SEM toward imaging nanobio materials without staining: Observation of insulin amyloid fibrils. (May 2017) - Ogawa, Takashi; Gang, Geun Won; Thieu, Minh Thu; Kwon, Hyuksang; Ahn, Sang Jung; Ha, Tai Hwan; Cho, Boklae
Highlights: Graphene and LV-STEM in SEM are effective to observe unstained nanobio materials. The method enables observation of insulin amyloid fibrils with widths of 7–8 nm. STEM shows a twisted ribbon structure of a fibril and SE shows its striped pattern. A low detection angle (15 mrad) is essential for STEM imaging of fibrils at 30 keV. Graphene can expand the operational energy range (5–30 keV) of LV-STEM. Abstract: Utilization of graphene-supporting films and low-voltage scanning transmission electron microscopy (LV-STEM) in scanning electron microscopy (SEM) is shown to be an effective means of observing unstained nanobio materials. Insulin amyloid fibrils, which are implicated as a cause of type II diabetes, are formed in vitro and observed without staining at room temperature. An in-lens cold field-emission SEM, equipped with an additional homemade STEM detector, provides dark field (DF)-STEM images in the low energy range of 5–30 keV, together with secondary electron (SE) images. Analysis based on Lenz's theory is used to interpret the experimental results. Graphene films, where the fibrils are deposited, reduce the background level of the STEM images compared with instances when conventional amorphous carbon films are used. Using 30 keV, which is lower than that for conventional TEM (100–300 keV), together with low detection angles (15–55 mrad) enhances the signals from the fibrils. These factors improve image quality, which enables observation of thin fibrils with widths of 7–8 nm. STEM imaging clearly reveals a twisted-ribbon structure of a fibril, and SE imaging shows an emphasized striped pattern of the fibril. The LV-STEM in SEM enables acquisition of two types of images of an identical fibril in a single instrument, which is useful for understanding the structure. This study expands the application of SEM to other systems of interest, which is beneficial to a large number of users. The method in this study can be applied to the observation of various nanobio materials and analysis of their native structures, thus contributing to research in materials and life sciences.